Curva de crescimento e acúmulo de matéria seca em couve-flor cultivada em substrato - de Oliveira Gondim, Ancelio Ricardo; Prado, Renato de Mello [UNESP]; Ribeiro Correia, Marcus Andre [UNESP]; Alves, Adriana Ursulino; Cecilio Filho, Arthur Bernardes [UNESP]; Politi, Lucas Sanches [UNESP] (Universidade Federal de Uberlândia (UFU), 2011)
Aiming to evaluate the curve of growth and dry matter accumulation in cauliflower cv. Verona in commercial substrate for vegetables Plantmax (R), an experiment was conducted in a greenhouse at UNESP, Jaboticabal, SP. The experimental design was randomized blocks with six treatments, five replicates, each plot had a plan. The treatments consisted of sampling times (20, 30, 40, 50, 60 and 70 days after transplantation). Evaluations of plant height, leaf number, stem diameter, leaf area, dry matter of shoot, root and whole plant, and fresh weight of the inflorescence. Furthermore, calculated the relative growth rate (RGR) of leaves, stems, roots, flowers and whole plant, presented in g day(-1) plant(-1). The hybrid of cauliflower 'Verona' shows initial slow growth, stepping up from 30 days after transplantation. The maximum accumulation of dry matter per plant was 87g at 70 DAT, with the participation of sheets of 53.8%, stem 9.9%, 30.7% of inflorescence and root 6.5%. The cultivation cauliflower Verona in substrate showed high accumulation of dry Inflorescence.

Com o objetivo de avaliar curva de crescimento e acúmulo de matéria seca na couve-flor cultivada em substrato, um experimento foi conduzido em casa de vegetação da UNESP, Campus de Jaboticabal, SP. O delineamento experimental foi de blocos ao acaso, com seis tratamentos e cinco repetições. Os tratamentos foram constituídos pelas épocas de amostragem (20; 30; 40; 50; 60 e 70 dias após o transplante). Avaliou-se a altura das plantas, o número de folhas, o diâmetro do caule, a área foliar, a matéria seca da parte aérea, da raiz e planta inteira. O máximo acúmulo de massa seca ocorre aos 70 (DAT), sendo de 87 g por planta. O híbrido de couve Verona apresenta crescimento inicial lento, intensificando-se a partir dos 30 dias após o transplante. O máximo acúmulo de massa seca total por planta foi de 87g, sendo a participação das folhas de 53,8%, caule de 9,9%, inflorescência de 30,7% e das raízes 6,5%.
Curve of growth and dry matter accumulation in cauliflower cultivated on substrate
Keywords: Brassica oleracea var.botrytis L; Absorption; Plant nutrition; Growth